Religious diversity and patrimonialization: A case study of the Nianli Festival in Leizhou Peninsula, China - Zheng, Shanshan (Approaching Religion, 2017)
With the emergence of the neologism ‘intangible cultural heritage’ in 2003 and the adoption of the Intangible Cultural Heritage Law of the People’sRepublic of China in 2011 various popular religious practices in China which used to be considered as feudal superstitions started to be recognized as examples of cultural heritage worthy of protection. If we examine the concept of religious diversity at a local level in contemporary China, the process of a ‘patrimonialization’ of popular religious practices that reflect the dynamic relationships which can be detected across diverse discourses, multiple stakeholders and cultural policies in different arenas could offer us a new perspective on religious practices to explore. In this article I offer an analysis, based on fieldwork conducted between 2013 and 2016 on the Leizhou Peninsula in southern China’s Guangdong Province, of the varying degrees of acceptance, accommodation and resistance prompted by the actualization of popular religious practices in this era of patrimonialization.